Picture map geography of South America. - Quinn, Vernon (New York J. B. Lippincott company, 1941)
South America has become a part of our world as never before. American boys and girls need to be familiar with their great neighbors, Argentina, Brazil and all the other countries that reach from Panama to Cape Horn. For it is certain that in a very short time there will be new meaning and ever-growing importance in Latin American tradem culture, travel and friendship.
Keywords: Country Studies